Modus operandi : a writer's guide to how criminals work - Corvasce, Mauro V., author; Paglino, Joseph R., author (Cincinnati, OH : Writer's Digest Books, 1995)
Find out how to give your mystery and detective novels that necessary grit of authenticity.
Arsonists -- Art, antique and jewel thieves -- Carjacking, hijacking, skyjacking and auto theft -- Con artists -- Counterfeiters and forgers -- Fencing -- Homicide -- Kidnapping -- Prostitution -- Armed robbery -- Safecracking and lockpicking -- Smuggling -- Shoplifters -- Whitecollar crime and money laundering.
Includes index.
Keywords: Crime; Criminal Psychology; Criminals; Forensic Sciences